Pengaruh Pelapisan dengan Emulsi Minyak Wijen dan Kelapa Sawit Mentah terhadap Rerata Susut Bobot, Total Padatan Terlarut dan Rerata Laju Respirasi pada Buah Manggis (Garcinia Mangostana L.) - Gede Arda; Ni Luh Yulianti (Fakultas Teknologi Pertanian, Universitas Udayana Gedung GA, Fakultas Teknologi Pertanian, Universitas Udayana Jl. Raya Bukit Jimbaran, Jimbaran, Kuta Selatan, Bali Telp/Fax: (0361) 701801, 2016)
The aims of this research were to obtain the best kind of coating material and consentrations ofnatural oil which could preserve the quality of mangosteen during storage. This research appliedComplete Randomized Design using 2 factor that was the kinds of natural oil (sesame oil, andcrude palm oil) and emulsion consentrations (1%, 5% to 20%, and 30%). In addition, eachtreatment was repeated twice to obtain 16 experimental units. Observed parameters were weightloss, Total Soluble Solid (TSS) and respiration rate of mangosteen during storage. According tothe results, there were found that the mangosteen coated using 30% sesame oil had the smallestpercentage of weight loss and Total Soluble Solid with about 4.89% and 16.98 °brix respectively.Respiration rate show that the oil concentration in emulsion was inversely proportional torespiration rate of mangosteen coated by that emulsion